Comparison of adhesion of thawed and cultured synovial mesenchymal stem cells to the porcine meniscus and the relevance of cell surface microspikes - Shunichi Fujii; Kentaro Endo; Nobutake Ozeki; Yuriko Sakamaki; Yuji Kohno; Mitsuru Mizuno; Hisako Katano; Kunikazu Tsuji; Hideyuki Koga; Ichiro Sekiya (BMC Molecular and Cell Biology, 2022)
Abstract Background Placement of a cultured synovial mesenchymal stem cell (MSC) suspension on a repaired meniscus for 10 min accelerated meniscus repair. Upon placement of the MSC suspension on the meniscus, microspikes projecting from the MSC surface trap meniscus fibers and promote MSC adhesion. Thawed cryopreserved MSCs are preferred materials for meniscus repair, as they can be transplanted without additional culture. However, the adhesion ability of thawed cryopreserved MSCs is unknown. Here, we compared the proportion of cultured versus thawed MSCs adhering to a porcine meniscus immediately and 10 min after placement. We also investigated the relationship between adhesion and the number of microspikes on the synovial MSCs. Methods Synovial MSCs were prepared from the knees of four donors with osteoarthritis. The “cultured MSCs” were thawed MSCs that were re-cultured and suspended in PBS for transplantation. A similarly prepared suspension was cryopreserved, thawed again, suspended in PBS, and used without further culture as the “thawed MSCs.” MSCs with at least three microspikes in SEM images were defined as microspike-positive MSCs. Porcine meniscus surfaces were abraded, cut into a cylindrical shape, and treated with MSC suspension. Non-adherent cells were counted immediately and again 10 min after placement to calculate the adhesion proportion. Results The proportion of microspike-positive MSCs was significantly higher in thawed (53 ± 3%) than in cultured (28 ± 5%) MSC suspensions. MSC adhesion to the meniscus was significantly better for the thawed than for the cultured MSC suspensions immediately after placement on the meniscus, but no differences were detected after 10 min. The proportion of MSCs with microspikes in the cell suspension was significantly correlated with the proportion of adhered MSCs immediately after the placement, but not 10 min later. Addition of FBS to the cryopreservation medium promoted a concentration-dependent increase in the proportion of microspike-positive cells. Conclusions Thawed MSCs adhered better than cultured MSCs immediately after placement, but adhesion was similar for both MSC preparations after 10 min. Immediately after placement, the presence of microspikes was associated with better adhesion of synovial MSCs to the meniscus.